Era uma vez... As metamorfoses nos contos de fadas contemporâneos - Theodoro, Ana Cláudia Nascimento (2012)
Thinking fairy tales are marvelous narratives that exist for centuries so we cannot even precise their origin is an intriguing thought. Because years can pass by and classical tales can still be known and recognized by children, adolescents and adults from worldwide. Along the storytelling of traditional tales whether they are about Red Riding Hood, Cinderella or Snow White underlying meanings are transmitted within the narratives that correspond with the dominant ideology of a society. Through the story s moral or the negative or positive ending of a character, for example, traditional fairy tales have lessons that aim at teaching the public and it is by means of models and ideologies that these stories mold boys and girls so they will know how to behave in society. Within the ideologies there are intrinsic meanings that relates to a patriarchal thought predominant in our culture, in which women are seen as passive, obedient and innocent human beings who must respect and accept men s will. So classical fairy tales have meanings that explicit sexism where woman is an individual incapable of controlling their own life, always needing men as a support. It is in front of such meanings confirming women as submissive that revisionism in fairy tale is made present, intending to question, to criticize or to subvert the stories moralized lessons. Along with postmodern and postcolonial theories, cultural and feminist studies, the carnavalization theory and parodic and intertextual elements that contemporary fairy tales such as the movies The princess and the frog, Shrek and literary fairy tales ―The courtship of Mr Lyon‖ and ―The Tiger s Bride‖ by Angela Carter propose an attitude for us to start looking again at the tales rethinking about the meanings that segregate women; the different and the excluded; the marginalized cultures treating them as inferior in order to shake the dominant structures that underlie in the stories. By means of metamorphosis occurred with the character or even inside the tale structure it is possible for the revisionism to, parting from feminist and postmodern perspectives, criticize, transgress, and also to propose alternatives related to gender, culture, society and ethnicity equality by means of valorizing the ones who are in the margin of contemporary society.